Estimating carbon sequestration cost function for developing countries - Nobi, Mohammad Nur (SLU/Dept. of Economics, 2013)
Carbon sequestration is considered as the cost effective way of reducing carbon dioxide emission and other greenhouse gases. This study estimated the carbon sequestration cost function considering land use change in developing countries. Using the instrumental variable method, this study found that the percentage change in the cost due to the percentage change in carbon sequestration is almost unitary. The result also shows that the presence of Clean Development Mechanism (CDM) project in a country and per capita GDP in purchasing power parity (GDP, ppp) have positive influence on the carbon sequestration cost function. The marginal cost calculated from the total cost function representing the unit price of carbon dioxide is very low compared with the marginal abatement cost of the developed countries but equals the price at the European CO2 emission trading market.